Biotechnology fundamentals - Khan, Firdos Alam (CRC Press, 2020)
"Biotechnology Fundamentals, Third Edition breaks down the basic fundamentals of this discipline, and highlights both conventional and modern approaches unique to the industry. The revised work presents new information on Forensic Science, Bioinformatics, Synthetic Biology, Biosimilars and Regenerative Medicine. In addition to recent advances and updates relevant to the previous edition, the revised work also covers ethics in biotechnology and discusses career possibilities in this growing field"-- Provided by publisher
Previous edition: 2016.
1. Introduction to Biotechnology. 2. Genes & Genomics. 3. Proteins & Proteomics. 4. Recombinant DNA Technology. 5. Microbial Biotechnology. 6. Plant Biotechnology. 7. Animal Biotechnology. 8. Environmental Biotechnology. 9. Medical Biotechnology. 10. Nanobiotechnology. 11. Industrial Biotechnology. 12. Trends in Biotechnology (Forensic Science, Synthetic Biology, Bioinformatics, Regenerative Medicine & Biosimilars). 13: Product Development in Biotechnology. 14: Ethics in Biotechnology. 15. Career in Biotechnology
Keywords: Biotechnology.; elektronické knihy; electronic books